It is currently 19 Jan 2018, 11:43

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

If √x -√y+√z=0, which of the following is true?

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Expert Post
Math Revolution GMAT Instructor
User avatar
D
Joined: 16 Aug 2015
Posts: 4692

Kudos [?]: 3319 [0], given: 0

GPA: 3.82
Premium Member
If √x -√y+√z=0, which of the following is true? [#permalink]

Show Tags

New post 28 Mar 2016, 21:43
Expert's post
9
This post was
BOOKMARKED
00:00
A
B
C
D
E

Difficulty:

  95% (hard)

Question Stats:

58% (01:50) correct 42% (02:13) wrong based on 151 sessions

HideShow timer Statistics

If \(√x -√y+√z=\)0, which of the following is true?

A. \(x^2+y^2+z^2=xy+xz+yz\)

B. \(x^2+y^2+z^2=2xy+2xz+2yz\)

C. \(x^2+y^2-z^2=2xy+2xz-2yz\)

D. \(x^2-y^2-z^2=xy+xz+yz\)

E. \(x^4+y^4+z^4=2xy+2xz+2yz\)


* A solution will be posted in two days.
[Reveal] Spoiler: OA

_________________

MathRevolution: Finish GMAT Quant Section with 10 minutes to spare
The one-and-only World’s First Variable Approach for DS and IVY Approach for PS with ease, speed and accuracy.
Find a 10% off coupon code for GMAT Club members.
“Receive 5 Math Questions & Solutions Daily”
Unlimited Access to over 120 free video lessons - try it yourself
See our Youtube demo

Kudos [?]: 3319 [0], given: 0

SC Moderator
User avatar
P
Joined: 13 Apr 2015
Posts: 1539

Kudos [?]: 1294 [0], given: 911

Location: India
Concentration: Strategy, General Management
WE: Information Technology (Consulting)
GMAT ToolKit User Premium Member CAT Tests
Re: If √x -√y+√z=0, which of the following is true? [#permalink]

Show Tags

New post 28 Mar 2016, 23:51
MathRevolution wrote:
If √x -√y+√z=0, which of the following is true?

A. x^2+y^2+z^2=xy+xz+yz
B. x^2+y^2+z^2=2xy+2xz+2yz
C. x^2+y^2-z^2=2xy+2xz-2yz
D. x^2-y^2-z^2=xy+xz+yz
E. x^4+y^4+z^4=2xy+2xz+2yz


\(\sqrt{x} + \sqrt{z} = \sqrt{y}\)

\(x + z + 2\sqrt{xz} = y\)

\(x + z - y = -2\sqrt{xz}\)

\((a + b + c)^2 = a^2 + b^2 + c^2 + 2ab + 2bc + 2ca\)

\(x^2 + z^2 + y^2 + 2xz - 2yz - 2xy = 4xz\)

\(x^2 + y^2 + z^2 = 2xy + 2yz + 2xz\)

Answer: B

Kudos [?]: 1294 [0], given: 911

Expert Post
Math Revolution GMAT Instructor
User avatar
D
Joined: 16 Aug 2015
Posts: 4692

Kudos [?]: 3319 [0], given: 0

GPA: 3.82
Premium Member
Re: If √x -√y+√z=0, which of the following is true? [#permalink]

Show Tags

New post 30 Mar 2016, 22:21
If √x -√y+√z=0, which of the following is true?

A. x^2+y^2+z^2=xy+xz+yz
B. x^2+y^2+z^2=2xy+2xz+2yz
C. x^2+y^2-z^2=2xy+2xz-2yz
D. x^2-y^2-z^2=xy+xz+yz
E. x^4+y^4+z^4=2xy+2xz+2yz


If you square the both equations, they become x+z+2√xz=y, x+z-y=-2√xz. If you once again square the both equations, x^2+z^2+y^2+2zx-2xy-2zy=4xz is derived and eventually becomes x^2+y^2+z^2=2xy+2yz+2zx.
Thus, the answer is B.
_________________

MathRevolution: Finish GMAT Quant Section with 10 minutes to spare
The one-and-only World’s First Variable Approach for DS and IVY Approach for PS with ease, speed and accuracy.
Find a 10% off coupon code for GMAT Club members.
“Receive 5 Math Questions & Solutions Daily”
Unlimited Access to over 120 free video lessons - try it yourself
See our Youtube demo

Kudos [?]: 3319 [0], given: 0

1 KUDOS received
PS Forum Moderator
avatar
P
Joined: 25 Feb 2013
Posts: 813

Kudos [?]: 381 [1], given: 42

Location: India
GPA: 3.82
GMAT ToolKit User Premium Member Reviews Badge CAT Tests
Re: If √x -√y+√z=0, which of the following is true? [#permalink]

Show Tags

New post 25 Dec 2017, 04:49
1
This post received
KUDOS
1
This post was
BOOKMARKED
MathRevolution wrote:
If √x -√y+√z=0, which of the following is true?

A. x^2+y^2+z^2=xy+xz+yz
B. x^2+y^2+z^2=2xy+2xz+2yz
C. x^2+y^2-z^2=2xy+2xz-2yz
D. x^2-y^2-z^2=xy+xz+yz
E. x^4+y^4+z^4=2xy+2xz+2yz


* A solution will be posted in two days.


In case one does not remembers the formula, plugging smart numbers will be highly effective.

Let \(x=z=1\) & \(y=4\). this satisfies our stem equation. Test the values in the options and the option where \(LHS=RHS\) will be correct

For Option B \(LHS=1^2+4^2+1^2=18\)

\(RHS=2*1*4+2*1*1+2*4*1=18\).

For other options, LHS will not be equal to RHS

Kudos [?]: 381 [1], given: 42

Intern
Intern
avatar
Joined: 16 Dec 2017
Posts: 1

Kudos [?]: 0 [0], given: 11

Re: If √x -√y+√z=0, which of the following is true? [#permalink]

Show Tags

New post 27 Dec 2017, 08:51
MathRevolution wrote:
If √x -√y+√z=0, which of the following is true?

A. x^2+y^2+z^2=xy+xz+yz
B. x^2+y^2+z^2=2xy+2xz+2yz
C. x^2+y^2-z^2=2xy+2xz-2yz
D. x^2-y^2-z^2=xy+xz+yz
E. x^4+y^4+z^4=2xy+2xz+2yz


If you square the both equations, they become x+z+2√xz=y, x+z-y=-2√xz. If you once again square the both equations, x^2+z^2+y^2+2zx-2xy-2zy=4xz is derived and eventually becomes x^2+y^2+z^2=2xy+2yz+2zx.
Thus, the answer is B.


Thank you. Could you help me understand where the highlighted portion came from?

Kudos [?]: 0 [0], given: 11

PS Forum Moderator
avatar
P
Joined: 25 Feb 2013
Posts: 813

Kudos [?]: 381 [0], given: 42

Location: India
GPA: 3.82
GMAT ToolKit User Premium Member Reviews Badge CAT Tests
If √x -√y+√z=0, which of the following is true? [#permalink]

Show Tags

New post 27 Dec 2017, 08:56
rb60006 wrote:
MathRevolution wrote:
If √x -√y+√z=0, which of the following is true?

A. x^2+y^2+z^2=xy+xz+yz
B. x^2+y^2+z^2=2xy+2xz+2yz
C. x^2+y^2-z^2=2xy+2xz-2yz
D. x^2-y^2-z^2=xy+xz+yz
E. x^4+y^4+z^4=2xy+2xz+2yz


If you square the both equations, they become x+z+2√xz=y, x+z-y=-2√xz. If you once again square the both equations, x^2+z^2+y^2+2zx-2xy-2zy=4xz is derived and eventually becomes x^2+y^2+z^2=2xy+2yz+2zx.
Thus, the answer is B.


Thank you. Could you help me understand where the highlighted portion came from?


Hi rb60006

we can rearrange the equation and write \(\sqrt{x}+\sqrt{z}=\sqrt{y}\), so on squaring it will be of the form \((a+b)^2=a^2+b^2+2ab\)

Kudos [?]: 381 [0], given: 42

Intern
Intern
avatar
Joined: 20 Oct 2017
Posts: 3

Kudos [?]: 0 [0], given: 44

Re: If √x -√y+√z=0, which of the following is true? [#permalink]

Show Tags

New post 09 Jan 2018, 07:31
Is this a 700 level question?

Kudos [?]: 0 [0], given: 44

PS Forum Moderator
avatar
P
Joined: 25 Feb 2013
Posts: 813

Kudos [?]: 381 [0], given: 42

Location: India
GPA: 3.82
GMAT ToolKit User Premium Member Reviews Badge CAT Tests
Re: If √x -√y+√z=0, which of the following is true? [#permalink]

Show Tags

New post 09 Jan 2018, 07:37
kritikalal wrote:
Is this a 700 level question?


Hi kritikalal

Check the "Tag" section just above the question. you will get all the details

Kudos [?]: 381 [0], given: 42

Re: If √x -√y+√z=0, which of the following is true?   [#permalink] 09 Jan 2018, 07:37
Display posts from previous: Sort by

If √x -√y+√z=0, which of the following is true?

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  


GMAT Club MBA Forum Home| About| Terms and Conditions| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.